Urban Futures : Planning for City Foresight and City Visions - Dixon, Timothy J., 1958-; Tewdwr-Jones, Mark (Book collections on Project MUSE., 2021)
City visions represent shared, and often desirable, expectations about our urban futures. This book explores the history and evolution of city visions, placing them in the wider context of art, culture, science, foresight and urban theory.